2019
DOI: 10.1088/1361-6595/ab07cc
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale investigation in the frequency domain of Ar/HMDSO dusty plasma with pulsed injection of HMDSO

Abstract: A combination of time-resolved optical emission spectroscopy measurements and collisionalradiative modeling is used to investigate the phenomena occurring over multiple time scales in the frequency domain of a low-pressure, axially asymmetric, capacitively coupled radiofrequency (RF) argon plasma with pulsed injection of hexamethyldisiloxane (HMDSO, Si 2 O(CH 3) 6). The collisional-radiative model developed here considers the population of argon 1s and all ten 2p levels (in Paschen's notation). The presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…The HMDSO flow is adjusted by a mass flow controller OMICRON switched by a pulse generator AGILENT. It was observed that, under particular conditions, namely an applied power below 60 W and an HMDSO duty cycle above 30%, the pulsed injection of the precursor induces periodic growth of dust, forming a cloud of nanoparticles between the two electrodes …”
Section: Experimental Setup and Diagnosticsmentioning
confidence: 99%
See 4 more Smart Citations
“…The HMDSO flow is adjusted by a mass flow controller OMICRON switched by a pulse generator AGILENT. It was observed that, under particular conditions, namely an applied power below 60 W and an HMDSO duty cycle above 30%, the pulsed injection of the precursor induces periodic growth of dust, forming a cloud of nanoparticles between the two electrodes …”
Section: Experimental Setup and Diagnosticsmentioning
confidence: 99%
“…On one hand, the presence of dust can increase the formation of H 2 by Eley–Rideal reactions on the surface of the nanoparticles. On the other hand, the presence of dust is known to increase the electron temperature which could influence the dissociation degree of HMDSO in the plasma, thus resulting in a rise of atomic and possibly molecular hydrogen . However, since dust formation follows a cyclic behavior, it implies that they grow simultaneously until a critical size is reached, leading to their loss by gravity .…”
Section: Plasma Sampling Mass Spectrometry Measurementsmentioning
confidence: 99%
See 3 more Smart Citations